Pengalaman Baby blues Syndrome Pada Ibu Postpartum di Kabupaten Merauke - Sitti Asma Kurniyati Laitupa; Endah Purwanti; Laili Nur Hidayati (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Background Postpartum blues, or better known as baby blues,